The Politics of Disinflation - Bob Hancké; Tim Vlandas (London School of Economics and Political Science (LSE), European Institute, 2017)
What explains the shift from the moderate to high inflation rates of the Golden Age of post-war capitalism to the low inflation regime of monetarism in the 1970s and 1980s? Conventional views emphasise the rise of monetarism as a new economic paradigm that convinced policy makers to delegate monetary policy to conservative and independent central banks – a view that comes in many variants, from constructivist to orthodox economics. In contrast to these arguments, we introduce electoral and party politics into the debate. This paper models and examines the shifts in the inflationary preferences of the median voter and their translation into party politics and economic policies. As the median voter accumulates nominal assets against a background of de facto and de jure increasing job security and rising wages, her preferences on macro-economic policies shift from concerns about employment-friendly to inflation-averse policies. Social democratic parties, who are pivotal players in this regard because of their 'natural' preference for high employment over low inflation, are thus forced to adopt antiinflation policies as well to remain electorally viable. We show that the employment situation of the average worker improved in every respect during the 1960s and 1970s, that most of the population became inflation averse during the 1970s and 1980s, and that social democratic parties were forced to adopt more economically orthodox party manifestos. We then analyse the shift to a low inflation regime in a series of country case studies.
Keywords: 330; inflation; Western Europe; Monetarism; Keynesianism; electoral politics